ANALISIS YURIDIS PEMBATALAN PUTUSAN PAILIT (STUDI PUTUSAN MAHKAMAH AGUNG NO. 834 K/Pdt. Sus/2009 TENTANG PEMBATALAN KEPAILITAN PT. CIPTA TELEVISI PENDIDIKAN INDONESIA) - , RIZKY ASTARI WIDYANTI, Pitaya S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research was to analyze The Supreme Court Decision Number 834 K/Pdt.Sus/2009 and analyze legal steps undertaken for the fulfillment of its accounts receivable lender. The research method used is a normative juridical approach. Source of data used are secondary data include primary legal materials, legal materials and secondary legal materials tertiary. Data analysis was performed by descriptive qualitative. The results showed that the existence of Global Crown Capital Limited and the debt to PT. Cipta Televisi Pendidikan Indonesia, still need evidence in the District Court because, in principle, proving the existence of creditors and debt at the Commercial Court of its simple (summier), so it is not the authority of the Commercial Court to prove the existence of the debt and his company. Regarding the steps taken by the lender after the annulment of the bankruptcy, the creditor can sue civilly to the District Court with default or unlawful act. The conclusion that the decision of the Supreme Court overturned the decision of the Commercial Court Number. 52/Pailit/2009/PN.NIAGA.JKT.PST, is in conformity with Act Number 37 of 2004 on Bankruptcy and Suspending the Obligation of Debt Payment.